SOCIAL MEDIA SHOULD BECOMING TOOL FOR ESTABLISH UNIVERSAL COMPASSION FOR ALL PEOPLE AS ONE SOLUTION TO SOLVE THE PANDEMIC COVID-19 PROBLEM - Prasanthy Devi Maheswari (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2023)
The Vedas state that humankind is the perfect creature. Humankind is the representation of God on the earth. However, because of the Kali-yuga character's effect, humankind and all things experienced degradation and even chaos. Sloka of Manusmṛti I.85 stated: "Of one kind is the virtue in the Kṛta yuga, different is it in the Tretà yuga. Of one kind is it in the Dvàpara yuga and different is it in Kali-yuga, successively and proportionately decreasing according to (to the spirit of) each age". (Deshpande, 2020:32). Degradation and chaos, which have been explained above, are not just theoretical, but they are real. Today, people tend to have higher education in this modern time, but destructive social competition and social conflict also continuously happen. In that situation, the other crucial problem, which is called pandemic Covid-19, makes most people panic. In the social panic situation, even many people used social media badly. Social media should be used to help people to communicate efficiently. In contrast, many people used to spread the hoax everywhere. According to the social conflict that simultaneously happened, we might arouse a question, Do we have to revisit the ancient values in our culture or our holly script? The hypothesis, in this case, is that we should re-look at the teaching of Bhagavadgita. The Bhagavadgita teaches that anything and everywhere, all of them are the same with us. If anyone makes to the other becoming chaos, it means it makes chaos for himself. The core of this teaching in the Veda called tat tvam asi is whether everyone can implement it; indeed, heaven is realized in the earth. This paper is a qualitative research based on Vedic texts and social reality. The goal of this research is social harmony supported by social media.